Foul play : Canadian true crime stories [videorecording (DVD)] (Filmhub, 2024)
Foul Play: Canadian True Crime Stories chronicles instances of major crime from across the Great White North. Based on real court records and police interview footage. Hosted by Kevin Jollimore.